The effect of using some of the tools and training aids in improving the performance level of some physical abilities and skills of volleyball players for juniors, ages 13-14 years - Kadhim, Sami; Adel, Omer; Saady, Souad (Journal of Physical Education, 2013)
The sportsman who practices volleyball should learn the basic skills in high accuracy in order to reach remarkable levels. The technological means and the training tools play a principal role in training process . The theoretical studies explained the using of instructional and training means in the dynamic learning . Research procedurs . The experimental schedule is used to convenient with research nature. A random sample of 28 young players aging between 13 – 14 years and they were divided in to tow groups ..control..and experimental . The researchers concluded that the assisting tools …means and instruments mad a big progress in elevating the physical capability level and skills . The researchers recommend the using of assisting means and tools in a various training programs as a developed approach for the physical and skill capability..and they recommend the specialized authorities to provide these means , specially for the young teams .